Professionalism in Medical Education: Constructing, Delivering, Assessing & Researching a Framework from a Malaysian Perspective - Jaiprakash Mohanraj, Heethal Jaiprakash (International Journal of Advanced Science and Technology, 2020)
Professionalization is concerned with the process of becoming a member of a profession. This includes processes of socialization and identity formation, in-other-words, taking on the features of a professional who defines that specific community(Irby & Hamstra, 2016). Medicine is an archetypal profession. The 2002 American Board of Internal Medicine Charter on Professionalism defined professionalism as “placing the interests of patients above those of the physician, setting and maintaining standards of competence and integrity and providing expert advice to society on matter of health”.The educational dilemma in defining professionalism exists because of the virtues and identities that it encompasses which invariably depends on the socio-economic, socio-cultural and political background that defines the physician’s role within the healthcare sector hence, in my view a search towards an ideal definition is futile as its acceptance will not be homogenous across the globe. Cultural background has a major influence on how an individual perceives professionalism(S. R. Cruess, Cruess, & Steinert, 2010; Hafferty, 2006).